2019
DOI: 10.3389/fpls.2019.01064
|View full text |Cite
|
Sign up to set email alerts
|

Early Extracellular ATP Signaling in Arabidopsis Root Epidermis: A Multi-Conductance Process

Abstract: Adenosine 5′-triphosphate (ATP) is an important extracellular signaling agent, operating in growth regulation, stomatal conductance, and wound response. With the first receptor for extracellular ATP now identified in plants (P2K1/DORN1) and a plasma membrane NADPH oxidase revealed as its target, the search continues for the components of the signaling cascades they command. The Arabidopsis root elongation zone epidermal plasma membrane has recently been shown to contain cation transport pathways (channel condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 81 publications
2
24
0
Order By: Relevance
“…Although the present study demonstrated the utility of the method in a microbiological setting, it is important to highlight that it is not limited to the use in prokaryotic organisms. Aside from roles in bacterial physiology, numerous studies reported different roles of eATP in eukaryotic organisms including human and plant physiology [ 17 , 39 , 47 ]. As a universal molecule of all living beings, eATP plays important roles in bacterial, animal and plant kingdoms, thus we believe that this method will allow elucidating the role and dynamics of eATP in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study demonstrated the utility of the method in a microbiological setting, it is important to highlight that it is not limited to the use in prokaryotic organisms. Aside from roles in bacterial physiology, numerous studies reported different roles of eATP in eukaryotic organisms including human and plant physiology [ 17 , 39 , 47 ]. As a universal molecule of all living beings, eATP plays important roles in bacterial, animal and plant kingdoms, thus we believe that this method will allow elucidating the role and dynamics of eATP in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that eATP-induced [Ca 2+ ] cyt increase in Arabidopsis roots requires plasma membrane Ca 2+ influx channels but the molecular identities of these channels remain unknown, as is also the case for other organs [ 9 , 11 , 14 , 21 , 22 , 23 ]. It has been hypothesized that the Arabidopsis annexin 1 protein (AtANN1) could be involved in mediating plasma membrane Ca 2+ influx [ 5 , 24 ] and recently AtANN4 was found to mediate eATP-induced [Ca 2+ ] cyt increase when expressed in Xenopus oocytes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two lectin receptor kinases, P2K1 and P2K2, were identified to be eATP receptors in Arabidopsis thaliana [ 19 , 20 ] involved in eATP-induced immune responses [ 13 , 14 , 21 ]. Signal transducers in the plasma membrane (PM), including heterotrimeric G proteins [ 12 , 22 ], NADPH oxidase [ 23 , 24 ], and Ca 2+ channels [ 6 , 23 , 25 , 26 ], were reported to be involved in eATP signal transduction. Several secondary messengers, e.g., ROS, H 2 O 2 , NO, and Ca 2+ may be responsible for the eATP-induced intracellular responses that eventually alter plant growth and development [ 6 , 17 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%